Genetic prediction of the effectiveness of biologics for psoriasis treatment. Issue 11 (30th April 2016) - Nishikawa, Rika; Nagai, Hiroshi; Bito, Toshinori; Ikeda, Tetsuya; Horikawa, Tatsuya; Adachi, Atsuko; Matsubara, Tsukasa; Nishigori, Chikako
Abstract: Anti‐tumor necrosis factor (TNF)‐α therapy is used for the treatment of psoriasis, with varying outcomes. However, the specific cause of inadequate response or treatment failure remains unknown. The aim of the present study was to identify useful clinical biomarkers for predicting therapeutic responses or to serve as new drug targets for refractory psoriasis cases. We performed a genome‐wide association study (GWAS) of 65 psoriasis patients who were prospectively followed after beginning anti‐TNF‐α therapy using Human Omni Express‐8 v1.2 Beadchips. Patients were enrolled at the dermatology departments of Kobe University Hospital and six collaborative hospitals. Associations between single nucleotide polymorphisms (SNP) and changes in the Psoriasis Area and Severity Index (PASI) after 12 weeks of treatment were evaluated. After genome data collection and quality control, a total of 731 442 SNPs were identified in 65 Asian psoriasis patients who were treated with adalimumab or infliximab. Here, we present 10 SNPs, such as those in JAG2 and ADRA2A, that were associated with treatment responses to anti‐TNF‐α agents (strongest effect, P < 7.11E‐06). This is the first GWAS to examine SNP associated with treatment responses in psoriasis patients. In addition, we identified other SNP that exhibited potential associations with anti‐TNF‐α treatment response, which merit further study. Of these, rs11096957 on TLR10, which is associated with increased TNF‐α production, was previously reported to be associated with treatment responses to TNF‐α inhibitors.